Effect of Non-Genetic Factors on Different Genetic Group of Buck’s Semen Quality and Quantity at National Livestock Breeding Center, Nepal (Nepalese Veterinary Journal, 2018)
This study was conducted to assess the quality and quantity aspects of different genetic group of buck’s semen used for Artificial Insemination (AI) at National Livestock Breeding Centre (NLBC), Pokhara. For this, records from different breeds and genetic groups of buck semen collected over 3 years (2014-2016) were analyzed. Parameters such as volume, density, mass motility, initial motility concentration and post thaw motility were analysed for various non-genetic factors like year, season, green based feeding. Data were analyzed by least square method using Harvey 1990 software package. The result showed that different genetic group of bucks (P